Effect Of Vitamin C On Tnf-Alpha Expression In Recurrent Tonsillitis At Rsud Dr. Moewardi - Kandhi, Putu Wijaya (Rumah Sakit Umum Daerah Dr. Moewardi, 2024)
Background: The immunopathogenesis of tonsillitis is thought to be due to the involvement of various proinflammatory cytokines including tumor necrosis factor α (TNF-α). Considering the role of TNF-α in the immunopathogenesis of tonsillitis, various interventions have been carried out both surgically and with drugs. Vitamin C, which is one of the important micronutrients in the body, has a role as an antioxidant and immunomodulator so that its administration is thought to be able to overcome the increase in TNF-α during the disease process. This study aims to determine the effect of vitamin C administration on TNF-α levels in patients with recurrent tonsillitis at Dr. Moewardi Hospital. Methods: This study is an experimental quantitative study using Randomized Controlled Trials research design with non-blinding. Samples in the study were divided into two treatment groups, namely treatment with oral vitamin C and placebo 50mg/kg body weight/day which then measured serum TNF-α levels. Results: The average TNF-α level in the Vitamin C group was smaller at 110.72 pg/mL compared to the control group which amounted to 148.96 pg/mL. The results of the independent t-test of TNF-α levels in both groups obtained a significant value <0.05, which was 0.037. This means that there is a significant difference in TNF-α levels between the two treatment groups. Conclusions: Vitamin C administration before tonsillectomy in patients with recurrent tonsillitis can significantly reduce TNF-α levels compared to the control group. This opens the possibility of routine use of vitamin C in recurrent tonsillitis patients to get better treatment results.